2015
DOI: 10.1101/024950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A resurrection experiment finds evidence of both reduced genetic diversity and potential adaptive evolution in the agricultural weedIpomoea purpurea

Abstract: This article contains supporting information online at: xxx.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…These results demonstrate that populations of a native plant with a restricted range are capable of responding to severe drought within a few years. Previous studies have demonstrated rapid evolution in plant populations in response to environmental changes, and many of these studies included weedy or introduced species with broad geographic ranges (e.g., Franks, ; Franks et al, ; Kuester et al, ; Parmesan, ; Sultan et al, ; Thomann et al, ), which can benefit from increased genetic variation from population mixing or hybridization during the invasion process (e.g., Gaskin & Schaal, ; Lavergne & Molofsky, ). In contrast, peripheral populations and species with restricted ranges have been viewed as potentially unable to respond quickly or effectively to a strong selective pressure due to lack of genetic variation (Dawson et al, ; Holt et al, ; Kirkpatrick & Barton, ; Pujol & Pannell, ; but see Sheth & Angert, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that populations of a native plant with a restricted range are capable of responding to severe drought within a few years. Previous studies have demonstrated rapid evolution in plant populations in response to environmental changes, and many of these studies included weedy or introduced species with broad geographic ranges (e.g., Franks, ; Franks et al, ; Kuester et al, ; Parmesan, ; Sultan et al, ; Thomann et al, ), which can benefit from increased genetic variation from population mixing or hybridization during the invasion process (e.g., Gaskin & Schaal, ; Lavergne & Molofsky, ). In contrast, peripheral populations and species with restricted ranges have been viewed as potentially unable to respond quickly or effectively to a strong selective pressure due to lack of genetic variation (Dawson et al, ; Holt et al, ; Kirkpatrick & Barton, ; Pujol & Pannell, ; but see Sheth & Angert, ).…”
Section: Discussionmentioning
confidence: 99%
“…The “resurrection” approach has recently emerged to document trait shifts (e.g., phenology) due to contemporary evolution (Dijk & Hautekèete, ; Franks et al, , ; Franks, Hamann, & Weis, ; Hairston et al, ; Kuester, Wilson, Chang, & Baucom, ; Sultan et al, ). This approach takes ancestral and descendent seeds collected from a population and raises them in a common environment.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of the populations sampled in 2003 had experienced glyphosate application (Kuester et al . ), they further experienced consistent glyphosate application between sampling periods, and on average, populations in 2012 exhibit slightly higher levels of resistance compared to the same populations from 2003 (Kuester et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), they further experienced consistent glyphosate application between sampling periods, and on average, populations in 2012 exhibit slightly higher levels of resistance compared to the same populations from 2003 (Kuester et al . ). Interestingly, we uncovered a significant interaction between sampling year and resistance for pistil height: the relationship between pistil height and resistance was negative in 2012 but positive in 2003.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation